UK Encryption Order Threatens Global Privacy Rights - Human Rights Watch (Human Rights Watch, 2025)
The United Kingdom government’s order to Apple to allow access to encrypted cloud data harms the privacy rights of users in the UK and worldwide.
United Kingdom